NILAI-NILAI PENDIDIKAN AKHLAK PERSPEKTIF IMAM NAWAWI AL-BANTANI DALAM KITAB NASHAIH AL-‘IBAD - Abdul Khamid (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
As we know that Imam Nawawi is a scholars of salaf thinkers who produce famous great works, he feels that it is very important that a person who has strong faith, perfection of aqidah and akhlak also quality and adequate of education must be possessed by everyone in their life. So the aims of this study is to find out and examine what education in the Nashaih al-'Ibad, the questions that will be answered through this research are: (1) how is the description of Imam Nawawi's thoughts about the values of moral education; (2) how is the relevance of the value of moral education by Imam Nawawi's thinking towards students today. To answer this question, this research using a library approach. The research method used is the type of literature, while the primary data source from the Nashaih al-‘Ibad book, and the source of the secondary from other books related to this research. The technical data analysis using inductive method and deductive method. The findings of this research indicate that the value of moral education in the Nashaih al-‘Ibad by Imam Nawawi al-Bantani is very much needed for the world of education today. From this it is hoped that a person who has good character and strong friendship will be realized.